Wage gap between immigrants and Canadian-born: The impact of immigration status and post- secondary education - Alves Mello, Daniela (Université d'Ottawa | University of Ottawa, 2015)
This paper investigates the issue of the wage gap between recent immigrants and their Canadian-born counterparts, when both groups have attained a post-secondary degree. The study builds on previous work carried out by numerous researchers to understand the environment immigrants face upon landing, and especially immigrants landed within a period of five to ten years. Even though immigrants have on average more years of schooling, the research shows that they earn less than their Canadian-born counterparts. Multiple reasons lead to this disparity, and addressing the issue is a complex task. The goal of this paper is to understand the causes of the wage gap. By understanding some of the major causes, this paper hopes to provide policymakers witha fresh view on this problem and a greater understanding of the subject. Finally, the paper proposes a set of recommendations to equip policymakers to act and reverse the trend of the widening wage gap between immigrants and their Canadian-born counterparts. Keywords: wage gap, immigrant, Canadian-born, immigrant status, human capital, post-secondary education, economic development, public policy, immigration, Canada Cet article analyse l’enjeu de l'écart salarial entre les nouveaux arrivants et leurs homologues nés au Canada qui ont obtenu un diplôme d'études postsecondaires. L'étude s’appuie sur des travaux antérieurs réalisés par de nombreux chercheurs pour comprendre l’environnement et les paramètres liés à l’établissement des nouveaux arrivants, particulièrement ceux arrivés au Canada durant les cinq à dix dernières années. La recherche montre que malgré que les nouveaux immigrants aient en moyenne plus d'années d'études, ils gagnent moins que leurs homologues nés au Canada. Plusieurs raisons expliquent cette disparité, et aborder cet enjeu est une tâche complexe. Le but de cet article est de comprendre les causes de l'écart salarial. En comprenant mieux les principales causes, cette étude espère doter les décideurs d’un nouveau regard sur cette problématique. Enfin, cette étude est accompagnée d'une série de recommandations qui visent à outiller les décideurs à agir pour inverser la tendance à l’accroissement des inégalités salariales entre les immigrants et leurs équivalents nés au Canada. Mots-clés: écart salarial, immigrant, né au Canada, statut d'immigrant, capital humain, éducation postsecondaire, développement économique, politique publique, immigration, Canada.